Empirical Essays on Stock Price Crash Risk - Magidou, Marina (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, Cyprus University of Technology, 2021)
Over the last decade, the literature examining the relationship between stock price crashes and their determinants has been undergoing a substantial development. The most prevalent explanation proposed by the literature so far, arises from the conceptual apparatus of agency theory and acknowledges the central role of managers in exploiting information asymmetry to withhold negative information from the investment community. The literature theorizes firm-specific stock price crash as an extreme negative value in the distribution of firm specific returns. However, this chapter brings to the fore a stark contrast between its definition as an outlier and the empirical occurrence of stock price crashes. The first chapter introduces the stock price crash risk puzzle by demonstrating a steadily growing trend on the stock price crash occurrences. Specifically, the incidence of firm-specific stock price crashes rises substantially from 5.5% in 1950 to 27% in 2018. This chapter offers empirical evidence suggesting that the two prominent agency-based channels proposed by crash literature, financial reporting opacity and overinvestment, offer a limited role in explaining the up-trending occurrences of stock price crashes. Furthermore, it is observed that important corporate governance functions exhibit noteworthy improvements. Finally, supplemental multivariate analysis conducted in this chapter, demonstrates that, especially when using the post SOX sample, there is a remarkable absence of any statistical relationship for either of the agency-based channels. The second chapter draws motivation from the findings of the first chapter and strives to illuminate the observed up-trending occurrences of stock price crashes. This chapter revisits the key role of CEOs and its linkage with future firm-specific stock price crash risk by providing empirical evidence suggesting a channel underpinning this association. Specifically, it synthesizes the existing empirical stock price crash literature that focuses on managerial characteristics and incentives. The empirical analysis provides evidence suggesting that, although the changes imposed to the regulatory regime shift firms to more transparent disclosures, and financial crisis acted as exogenous disciplining shock on management to avoid squandering funds by overinvesting, some of the managerial characteristics and incentives can still consist an explanation for the stock price crash occurrences. However, while the CEO-crash relationship is still apparent, and the explanatory power of the agency-based channels has attenuated as time wears on, managers are seeking for alternative channels to retain/inflate investor’s expectations and subsequently the level of stock prices, to safeguard against potential legal jeopardy. This chapter proposes a new channel, the managerial rhetoric channel, which is employed as a vital conduit through which managers convey information to the investment community and shape investors’ expectations. Managerial rhetoric in corporate reports featuring positive tone sentiment and discussions of technology and innovation activities is positively associated with one year ahead stock price crash risk. The third chapter investigates managerial opportunistic behavior in the years prior to CEO departures. The findings show that the occurrence of a stock price crash is heightened prior to the departure of the CEO. Specifically, one and two years before the CEO departure, firms experience 24.5% and 23.9% more stock price crashes than the rest years of CEO tenure. This phenomenon has been ascribed to a “crepuscular behavior”, whereby CEOs in their final years in office appear to act opportunistically by overly hiding negative news from investors. This behavior has certain wealth effects because, for instance, departing CEOs appear to significantly reduce their options and stock ownership, in comparison with their non-departing peers. Finally, this chapter investigates the corporate governance environment implications surrounding CEO departures.
Keywords: Stock price crashes; Bad news hoarding; Agency theory; Stock price crash channels; Corporate governance; Managerial characteristics; Managerial incentives; Managerial rhetoric channel; Managerial myopia; Short-termism; CEO departure